Multichannel bioelectronic sensing using engineered Escherichia coli - Xu Zhang; Marimikel Charrier; Caroline M. Ajo-Franklin (Nature Communications)
Abstract To advance environmental health and hazard detection, researchers have developed whole-cell bioelectronic sensors by engineering extracellular electron transfer to be dependent on an analyte1. However, these sensors regulate a single electron transfer pathway as an electrochemical channel, limiting the sensing information to a single analyte. We have developed a multichannel bioelectronic sensor where different chemicals regulate distinct extracellular electron transfer pathways within a single Escherichia coli cell. One channel utilizes the flavin synthesis pathway from Bacillus subtilis 2 and is controlled by a cadmium-responsive promoter. Another channel, the CymA-Mtr pathway from Shewanella oneidensis 3, is controlled by an arsenite-responsive promoter and activates cytochrome CymA expression4,5. We exploit the differing redox potentials of the two extracellular electron transfer pathways6 to develop a redox-potential-dependent algorithm that efficiently converts biological signals into 2-bit binary outputs. This enables our bioelectronic sensor to detect and differentiate heavy metals at EPA limits. When deployed in complex environmental water samples, our sensor effectively and accurately encodes 2-bit binary signals across various analyte conditions. Thus, our multichannel bioelectronic sensor advances the field through simultaneous detection of different chemicals by a single cell, significantly expanding information transmission and helping to safeguard human and environmental health.